Close cooperation between science, management and industry benefits sustainable exploitation of the Falkland Islands squid fisheriesa. Issue 4 (12th June 2013) - Arkhipkin, A.; Barton, J.; Wallace, S.; Winter, A.
<x xml:space="preserve">Abstract</x> The Falkland Islands fishing industry is unique, as 60–80% of its annual catch consists of two squid species, Illex argentinus and Doryteuthis gahi. Short annual life cycles make both species susceptible to intra‐annual environmental changes, resulting in large biomass fluctuations that must be addressed in management of the stocks. In the D. gahi fishery, short chains of communication between science, management and industry allow effective cooperation in the interest of long‐term sustainable exploitation. The industry is responsive to short‐notice requests for in‐season information about the fishery. Management takes into account both scientific advice and industry recommendations, through ongoing consultations before and during the fishing seasons. As a result of this cooperation, D. gahi is one of the best managed squid fisheries in the world with local fishing companies being amongst the largest and most profitable enterprises in the Falklands economy. The I. argentinus fishery has the same potential, but a further level of cooperative management is needed as this squid is a straddling stock between several countries and the high seas. Development of a regional fisheries management organization in the South Atlantic Ocean is required to control multilateral exploitation and ensure long‐term sustainability of I. argentinus stocks.